2020
DOI: 10.1519/jsc.0000000000003749
|View full text |Cite
|
Sign up to set email alerts
|

A 28-Day Carbohydrate-Restricted Diet Improves Markers of Cardiovascular Disease in Professional Firefighters

Abstract: Waldman, HS, Smith, JW, Lamberth, J, Fountain, BJ, Bloomer, RJ, Butawan, MB, and McAllister, MJ. A 28-day carbohydrate-restricted diet improves markers of cardiovascular disease in professional firefighters. J Strength Cond Res 34(10): 2785–2792, 2020—This study compared the effects of a 4-week, nonketogenic, carbohydrate-restricted (<25% of calories) diet (CRD) on markers of inflammation and oxidative stress in professional firefighters (FF). Subjects (n = 15) reported to the laboratory for 2 sessions (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, it may lead to CVD risks due to increases in LDL cholesterol and very-low-density lipoprotein [ 52 ]. Another study by Waldman et al [ 47 ] used biomarker measurements to further assess the utilization of a 28-day CRD to improve cardiometabolic health. Their results suggest that a 28-day CRD can improve biomarkers of CVD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it may lead to CVD risks due to increases in LDL cholesterol and very-low-density lipoprotein [ 52 ]. Another study by Waldman et al [ 47 ] used biomarker measurements to further assess the utilization of a 28-day CRD to improve cardiometabolic health. Their results suggest that a 28-day CRD can improve biomarkers of CVD.…”
Section: Resultsmentioning
confidence: 99%
“…35 The preparatory critical training phase for WLFFs 33,34 and the Alaskan backcountry hunting expeditions [33][34][35][36] differ in the availability or consumption of dietary nutrients, wherein WLFFs are typically well fed but Alaskan backcountry hunters experience high levels of energy deficit (À 10 to -9 MJ day À1 ). Variations in energy balance are therefore important in that multi-day bouts of moderate intensity physical activity typically produce favorable outcomes in serum lipid remodeling and body composition changes 37 ; a finding that does not appear to result following the multifactorial stressors associated with seasonal wildfire suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small sample size and limited duration, more research is needed to further explore the potential impact a low-carbohydrate diet may have on the health and performance of first responders. In addition, a notable observation by Waldman et al [ 310 ] highlighted the previous findings by Yang et al [ 295 ] that indicated firefighter populations prefer a diet higher in animal proteins, which may increase feelings of satiety and naturally decrease overall caloric intake. Therefore, it is likely not the decrease in carbohydrates but rather the increase in protein consumption that makes the adoption of a CRD an effective nutrition intervention for fire communities.…”
Section: Part 2 – First Respondersmentioning
confidence: 92%